Impact of Climate Change on the Fishermen’s Livelihood Development: a case study of village in Coromandel Coast - Srikanthan, S. (University of Jaffna, 2013)
This study analyzes the impact of climate change on fisherman livelihood development. Climate change is defined a change in the statistical properties of the climate system in particular region when considered over long periods of time, regardless of cause. However it is classified into two categories namely predictable and unpredictable climate change based on the discussion with village dwellers. In this paper, those climate change or weather condition that may occur in coming time could be predicated in advance is defined as predictable climate change for example cyclone and those climate change or weather condition could not be predictable in advance is defined as unpredictable climate change on the fishermen livelihood development. It has gained a few attentions from the social science researches. The data for this study were collected through informant case studies from fishing village of Pommaiyar Palaiyam located in Coromandel Coast, Tamil Nadu, India during the intensive fieldwork period of doctoral research, and the qualitative approaches are used for analyzing the data. The finding of this study explores the correlation between the unpredictable climate change and multi- dimensional paradigm of poverty of the proposed study village as follows (1) the climate change of the village from the last two years,(2) the impact of unpredicted climate change on fishermen livelihood development activities: occupation uncertainty income disorganization, damages, loses of fishing equipment and psycho- social problem, and (3) the suggestions and recommendation from this issue. This study analyzed their social problem especially multi- dimensional poverty with the concept of vicious circle which is a key factor for their prolonged poverty and psycho- social problem which is a barrier for livelihood development activities uplifting of this village and suggests that the measures to be taken to reduce the present scenario of the people.
Keywords: livelihood development; unpredictable climate change; poverty; natural disaster Indian Coromandel Coast.